Review: fish collagen: extraction, characterization and application in wound healing and drug delivery - Nguyen Thuy Chinh; Thai Hoang (Vietnam Journal of Science and Technology, 2024)
Collagen is a natural protein presenting in the animal and human’s body. It is in natural fibrous and could be found in the connective tissue and flesh of mammal, approximately 25-35 wt.% of total human protein. Collagen is abundant in fibrous tissues such as: bones, cartilage, tendons, blood vessels, ligaments, skin, cornea, aortic disc and intestines. Fish collagen is currently being studied as a new biological substitute for collagen from animals. It extracted from by-products (scales, skins, bones, etc.) by biochemical or biological methods is safe, has high adsorption, high compatible. The factors influencing on the extraction process include temperature, time, concentration of ingredients, etc. The fish collagen is usually collagen type I with a fibril structure. Each unit of collagen is tropocollagen consisting of three polypeptide chains twisted together. Depending on the source of ingredients, the composition of aminoacids, denaturation temperature, the sequence of aminoacids, structure, morphology, molecular weight, extraction yield, etc. of obtained collagens are different. This paper reviews the extraction and characterization of fish collagen from products after fish processing by chemical or biochemical methods. The applications of fish collagen in wound healing and drug delivery are also reviewed.